Identification of Fusarium virguliforme FvTox1-Interacting Synthetic Peptides for Enhancing Foliar Sudden Death Syndrome Resistance in Soybean. - Bing Wang; Sivakumar Swaminathan; Madan K Bhattacharyya (PLoS ONE)
Soybean is one of the most important crops grown across the globe. In the United States, approximately 15% of the soybean yield is suppressed due to various pathogen and pests attack. Sudden death syndrome (SDS) is an emerging fungal disease caused by Fusarium virguliforme. Although growing SDS resistant soybean cultivars has been the main method of controlling this disease, SDS resistance is partial and controlled by a large number of quantitative trait loci (QTL). A proteinacious toxin, FvTox1, produced by the pathogen, causes foliar SDS. Earlier, we demonstrated that expression of an anti-FvTox1 single chain variable fragment antibody resulted in reduced foliar SDS development in transgenic soybean plants. Here, we investigated if synthetic FvTox1-interacting peptides, displayed on M13 phage particles, can be identified for enhancing foliar SDS resistance in soybean. We screened three phage-display peptide libraries and discovered four classes of M13 phage clones displaying FvTox1-interacting peptides. In vitro pull-down assays and in vivo interaction assays in yeast were conducted to confirm the interaction of FvTox1 with these four synthetic peptides and their fusion-combinations. One of these peptides was able to partially neutralize the toxic effect of FvTox1 in vitro. Possible application of the synthetic peptides in engineering SDS resistance soybean cultivars is discussed.